An unusual presentation revealing pancreatic carcinoma: Sister Mary Joseph Nodule - Sghir, Hafida; Jellal, Soumia; Errami, Adil Ait; Oubaha, Sofia; Samlani, Zouhour; Krati, Khadija (Global Journal of Medical and Clinical Case Reports, 2019)
Sister Mary Joseph Nodule (SMJN) is a cutaneous nodule resulting from metastasis of malignant tumors affecting the umbilicus; it had been reported in 0.7e10.4% of patients. This case report describes an 82-year-old male diagnosed with metastatic pancreatic adenocarcinoma and confirmed by the biopsy of Sister Mary Joseph’s nodule. The aim of this presentation is too aware of such a specific manifestation, enables the physicians to investigate the underlying malignancy and to show the role of biopsy of the nodule for the diagnosis of the primitive cancer.